2019
DOI: 10.1111/nph.16124
|View full text |Cite
|
Sign up to set email alerts
|

Thermal imaging as a noninvasive technique for analyzing circadian rhythms in plants

Abstract: Endogenous (~24 circadian) rhythms control an enormously diverse range of processes in plants and are, increasingly, the target of studies aimed at understanding plant performance. Although in the previous few decades most plant circadian research has focused on Arabidopsis, there is a pressing need for low-cost, high-throughput tools for analyzing rhythms in a wider variety of species. The present contribution investigates using circadian temperature oscillations as a novel marker for assaying plant circadian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 52 publications
2
19
0
Order By: Relevance
“…The dicot and monocot leaf surface temperature displays robust circadian rhythm (Dakhiya & Green, 2019), which indicates that plants respond to the fluctuations of environmental temperature during the day, and regulate the loss or preservation of water from the leaf through transpiration system. To find out how GmLCLs affect the response of leaves to water shortage, we performed analysis on physiological leaf trait at different times during the day.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dicot and monocot leaf surface temperature displays robust circadian rhythm (Dakhiya & Green, 2019), which indicates that plants respond to the fluctuations of environmental temperature during the day, and regulate the loss or preservation of water from the leaf through transpiration system. To find out how GmLCLs affect the response of leaves to water shortage, we performed analysis on physiological leaf trait at different times during the day.…”
Section: Resultsmentioning
confidence: 99%
“…Here, mutation of GmLCL caused a significant increase in leaf temperature in drought‐resistant leaves (Figure 4a,b). Leaf temperature is known to be regulated by the circadian clock and exhibits a free‐oscillating rhythm (Dakhiya & Green, 2019). It is reported that the modulation of leaf temperature largely depends on plant transpiration, and transpiration intensity is partially regulated by the circadian movement of stomata, which has been observed in many species (Gorton et al, 1989; Hassidim et al, 2017; Martin & Meidner, 1971; Sayre, 1926).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, it is interesting to quantify the impact of environmental tress (e.g., cold) on the normal growth rhythms if we know the mechanism of the biological clock. Finally, the seasonal and circadian rhythms were studied using TLS data only; multisource remote sensing data are expected to use, such as using hyperspectral, thermal, and chlorophyll fluorescence to track the physiological rhythms [ 12 , 64 ]. Meanwhile, simultaneous measurement of changes in plant physiology (e.g., stomatal movement), biochemistry, and metabolite indicators have important prospects for explaining changes in plant structural rhythms [ 7 , 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Plant structural rhythm is regulated by both the biological clock and environment, which can directly capture plant structure dynamics and their relationships with plant functions [ 10 ]. It is becoming a promising direction to understand plant rhythm which is now more easily accessible with the development of sensing technologies, computer vision, and deep learning algorithms [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thermography also appears as a very convenient tool to study other aspects of plants that are out of the scope of this review, such as seeds vigor [173], investigations on circadian rhythms [174,175], the effects of microgravity on plant physiology [176], interactions with plant-symbiotic microorganisms [177][178][179][180], the impact of climate change in ecology [15], or food industry [181]. Thermography is also a very relevant tool for screening for mutants [182,183] and cultivars [21] with desirable phenotypes such as pathogen resistance or improved performance upon certain abiotic stress conditions.…”
Section: Uses Of Plant Thermography For Agriculture In the Near Futurementioning
confidence: 99%